Social Media’s Effect on Visiting Intention of Regenerative Tourism: Case Study of A Regenerative Tourism Destination - Adi, Antonius; Palupi, Santi; Bong, Tania (E-Journal of Tourism; Volume 11 Number 2 (September 2024), 2024)
The concepts of Sustainable Tourism has developed to many practices. One of the practices is Regenerative Tourism. The Role of Social Media on promoting the Regenerative Tourism has played an important Role in promoting the destination yet Regenerative Tourism Sites remain underexposed. The Purpose of this research is to analyze the effect of Social media Marketing on Visiting Intention and Destination Intention of a Regenerative Tourism Destination. as one of the Regenerative Tourism Destination. Methodology of this research is hypothesis Testing the causal effect of Social media marketing toward Destination Image and Visiting Intention. Partial Least Squares Structural Equation Modeling were chosen as the method to analyze the data. The Software used is SmartPLS4 and 100 Samples is analyzed. The results shows that Social Media Marketing affect Destination Image and Visiting Intention Significantly.